New concept of Si–Fe based sintered soft magnetic composite. (29th May 2015) - Schäfter, T.; Burghaus, J.; Pieper, W.; Petzoldt, F.; Busse, M.
<x content-type="archive" xml:space="preserve">Abstract</x> The present paper introduces a new concept of a sintered soft magnetic composite (SSC): a combination of a sintered soft magnet and soft magnetic composite. The approach is to create a Fe–Si based bulk material with a microstructure of Si rich, highly insulating ferromagnetic particle boundary phases by a high temperature heat treatment (sintering). The concept is realised via a powder metallurgical route, starting from an initial mixture of iron, silicon and copper. Silicon forms a graded boundary phase around the iron particles. Copper is added to reduce the melting point of the silicon and to ensure a uniform wetting of the silicon-rich layer around the iron particles. A systematic composition range of such sintered materials are evaluated as to magnetic and mechanical properties. The best material composition found has 96 wt-% iron+3 wt-% silicon+1 wt-% copper with the optimum sintering parameters of 1050 to 1100°C for 30 min in a nitrogen atmosphere.